Profiles of PhD students’ satisfaction and their relationships with demographic characteristics and academic career enthusiasm - Yang, Yang; Cai, Jianqiao (Frontiers in Psychology, 2022)
Doctoral students' satisfaction is of great importance to the quality of higher education. Using a person-centered approach, this study examined the possible PHD students’ satisfaction profiles to better understand the individual differences in PHD students feeling about the training process. 4964 participants were included in this study, and the results of latent profile analysis revealed that they can be identified into four subgroups: low-low group (700, 14.1% of the sample), low motivation-high hygiene group (979, 19.7% of the sample), high motivation-low hygiene group (1554, 31.3% of the sample), and high-high group (1731, 34.9% of the sample). Analyses showed that PhD students differed significantly in gender, age, country, study abroad status, work status, and caring responsibilities depending on satisfaction profiles membership. Besides, both motivator factors and hygiene factors have positive effects on the changes in academic career enthusiasm of PhD students, but the effect of motivator factors presented a stronger irreplaceability.